1991
DOI: 10.3109/10408449109019571
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Cavity Enzymes Involved in Xenobiotic Metabolism: Effects on the Toxicity of Inhalants

Abstract: A decade ago, the ability of nasal tissues to metabolize inhalants was only dimly suspected. Since then, the metabolic capacities of nasal cavity tissues has been extensively investigated in mammals, including man. Aldehyde dehydrogenases, cytochrome P-450-dependent monooxygenases, rhodanese, glutathione transferases, epoxide hydrolases, flavin-containing monooxygenases, and carboxyl esterases have all been reported to occur in substantial amounts in the nasal cavity. The contributions of these enzyme activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(77 citation statements)
references
References 115 publications
3
74
0
Order By: Relevance
“…These enzymes may also protect the central nervous system against inhaled toxicants. P450 enzymes are, however, also central for the metabolic activation of foreign compounds into reactive, toxic metabolites, and olfactory P450s have been suggested to play a key role in the tissue-selective toxicity of drugs and chemicals in this tissue (Gaskell, 1990;Dahl and Hadley, 1991;Reed, 1993;Brittebo, 1997;Ding and Kaminsky, 2003). A decreased olfactory toxicity has been demonstrated after pretreatment with various P450 inhibitors (Brandt et al, 1990;Genter et al, 1994;Bahrami et al, 2000b).…”
mentioning
confidence: 91%
“…These enzymes may also protect the central nervous system against inhaled toxicants. P450 enzymes are, however, also central for the metabolic activation of foreign compounds into reactive, toxic metabolites, and olfactory P450s have been suggested to play a key role in the tissue-selective toxicity of drugs and chemicals in this tissue (Gaskell, 1990;Dahl and Hadley, 1991;Reed, 1993;Brittebo, 1997;Ding and Kaminsky, 2003). A decreased olfactory toxicity has been demonstrated after pretreatment with various P450 inhibitors (Brandt et al, 1990;Genter et al, 1994;Bahrami et al, 2000b).…”
mentioning
confidence: 91%
“…2). The slow increase in lateral activity could be caused by the products of nasal chemical reactions catalyzed by various enzymes (21). Previous research has shown that the chemical reactions in the nasal cavities are capable of breaking down the odor molecules into smaller molecules (22).…”
Section: Modification Of Saps With Prolonged Exposurementioning
confidence: 99%
“…The nasal tissues, both olfactory and respiratory, contain high amounts of numerous enzymes capable of metabolizing inhaled vapors (for a review see Dahl and Hadley, 1991). Among those enzymes, oxidoreductases, carboxylesterases, and cytochrome P-450 are likely to metabolize many of the VOCs shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%